Facile microwave-assisted green synthesis of ZnO nanoparticles: application to photodegradation, antibacterial and antioxidant - Mallikarjunaswamy, C.; Lakshmi Ranganatha, V.; Ramu, Ramith; Udayabhanu; Nagaraju, G. (Journal of materials science. Materials in electronics, 2020)
The present study reports the effective synthesis of zinc oxide nanoparticles (ZnO Nps) by microwave irradiation method using Indian bael ( Aegle marmelos ) juice as fuel. The synthesized nanostructures were characterized by X-ray diffraction, FT-IR, scanning electron microscope, transmission electron microscope, Raman Spectroscopy, photoluminescence and ultraviolet (UV)–visible studies. At room temperature, photoluminescence spectrum showed the excitation wavelength at 370 nm and emission peaks at 388 and 468 nm corresponding to Zn vacancies and O vacancies, respectively. Further, the effectiveness of the synthesized zinc oxide nanoparticles was tested for methylene blue dye degradation under UV irradiation. The dye removal efficiency of nanoparticles was 96% after 35 min of UV ( λ = 617 nm) irradiation. The ZnO nanoparticles were subjected to antimicrobial activity against different strains. The current synthetic work pledges to provide some new visions into the design of nanomaterial for multifunctional long-term applications for cleanup and biomedical applications.